2020
DOI: 10.24052/jbrmr/v14is02/art-06
|View full text |Cite
|
Sign up to set email alerts
|

Exploring electronic -loyalty antecedents in Egyptian commercial banks; Electronic customer relationship management and banking electronic satisfaction

Abstract: Identifying factors that influence customer's e-loyalty is paramount for commercial banks to develop successful marketing strategies to form a broad base of customers that practice online transaction. So, this study aimed to investigate the impact of Electronic Customer Relationship Management (E-CRM) dimensions (customization strategy, electronic communication channels) on Electronic loyalty of customers through electronic banking satisfaction as a mediator Variable in Egyptian commercial banks. A quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This is because it facilitates the service usage by customers and makes it more cost-effective. Similar findings are also shown in the studies of Hashemzadeh et al (2011), Khan et al (2022), Kumar et al (2021), Mohamed et al (2022) and Rashwan et al (2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is because it facilitates the service usage by customers and makes it more cost-effective. Similar findings are also shown in the studies of Hashemzadeh et al (2011), Khan et al (2022), Kumar et al (2021), Mohamed et al (2022) and Rashwan et al (2020).…”
Section: Discussionsupporting
confidence: 90%
“…This led to higher service quality and better connection and interaction with their customers, which resulted in improved levels of customer satisfaction. Rashwan et al (2020) revealed that due to the technology-based CRM used by businesses, customers have easier access to services, at any time, from anywhere, and at a lower cost, and they can customize their services based on their needs and preferences. According to the authors, this increased customer satisfaction with service providers and impacted higher loyalty rates.…”
Section: Technology-based Crm and Customer Satisfactionmentioning
confidence: 99%